Exogenous 10 kDa-Heat Shock Protein Preserves Mitochondrial Function After Hypoxia/Reoxygenation - Maciel, Leonardo; de Oliveira, Dahienne Ferreira; Monnerat, Gustavo; Campos de Carvalho, Antonio Carlos; Nascimento, Jose Hamilton Matheus (Frontiers in Pharmacology, 2020)
Humoral factors released during ischemic preconditioning (IPC) protect the myocardium against Ischemia/Reperfusion (I/R) injury. We have recently identified 10kDa-heat shock protein (HSP10) and a fraction of small 5-10kDa peptides (5-10sP) in the coronary effluent of IPC-treated hearts and demonstrated their cardioprotective potential. We here used our isolated mitochondria model to characterize the impact of exogenous HSP10 and 5-10sP on mitochondria function from myocardium subjected to I/R injury. Isolated perfused rat hearts were submitted to 30-min global ischemia and 10-min reperfusion. Before ischemia, isolated hearts were infused with saline or 5-10sP, with or without a mitochondrial ATP-sensitive-K+-channel blocker (5HD 10μmol·L-1) or PKC inhibitor (Chelerythrine 10μmol·L-1), before I/R. HSP10 (1µmol·L-1) was infused into isolated hearts before I/R without blockers. At 10-min reperfusion, mitochondria were isolated and mitochondrial function was assessed. In a subset of experiments, freshly isolated mitochondria were directly incubated with HSP10 or 5-10sP with or without 5HD or chelerythrine before in vitro hypoxia/reoxygenation. Infusion of 5-10sP (n=5) and HSP10 (n=5) into isolated hearts before I/R, improved mitochondrial ADP-stimulated respiration, ATP production, and prevented mitochondrial ROS formation compared to I/R group (n=5), this effect was abrogated by 5HD and chelerythrine. In freshly isolated mitochondria with in vitro hypoxia/reoxygenation, HSP10 (n=16) and 5-10sP (n=16) incubation prevented reductions of mitochondrial ADP-stimulated respiration (91.5±5.1 nmol O2/min/mg PTN), ATP production (250.1±9.3 μmol ATP/200μg PTN), and prevented mitochondrial ROS production (219.7±9.0 nmol H2O2/200μg PTN) induced by hypoxia/reoxygenation (n=12, 51.5±5.0 nmol O2/min/mg PTN; 187±21.7 μmol ATP/200μg PTN; 339.0±14.3 nmol H2O2/200μg PTN, p<0.001, respectively). 5HD reduced the ADP-stimulated respiration in the HSP10 group (65.84±3.3 nmol O2/min/mg PTN), ATP production (193.7±12.1 μmol ATP/200μg PTN) and increased ROS in the 5-10sP group (274.4±21.7 nmol H2O2/200μg PTN). Mitochondria are a target of the cardioprotection induced by 5-10sP and HSP10. This protection is dependent of PKC and mKATP activation. HSP10 can act directly on mitochondria and protects against hypoxia/reoxygenation injury by mKATP activation.